2021
DOI: 10.5688/ajpe8378
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Virtual Skills-based Assessments Focused on Communication

Abstract: Objective. To evaluate faculty and student perceptions and performance of virtual compared to in-person skills-based assessments focused on communication. Methods. Providing sufficient formative and summative feedback is a challenge, particularly in the context of skills-based assessments. In spring 2020, two 12-item questionnaires, one each for students and faculty, were designed to assess perceptions of virtual skills-based assessments. The survey was distributed via QuestionPro© to second and third professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…However, students in this study agreed that there were differences in "difficulty, stress, interpreting patient cues, and in maintaining eye contact and tone of voice between the two means of consultation" [7]. Recently, VanLangen and colleagues found virtual skills-based assessments to be an appropriate mechanism to assess student communication skills; however, they did not observe a strong preference for virtual skills-based assessments in the future [8]. Similar research from nursing and medicine describes telehealth OSCE simulation yet fails to explore student perspectives [9,10].…”
Section: Introductionmentioning
confidence: 61%
“…However, students in this study agreed that there were differences in "difficulty, stress, interpreting patient cues, and in maintaining eye contact and tone of voice between the two means of consultation" [7]. Recently, VanLangen and colleagues found virtual skills-based assessments to be an appropriate mechanism to assess student communication skills; however, they did not observe a strong preference for virtual skills-based assessments in the future [8]. Similar research from nursing and medicine describes telehealth OSCE simulation yet fails to explore student perspectives [9,10].…”
Section: Introductionmentioning
confidence: 61%
“…25 Recently, patient counseling and communication skills were assessed via virtual platforms whereby students and faculty considered the virtual assessment appropriate in assessing student communication skills, however, a strong preference for future virtual skills-based assessments was not observed. 35 In our study, despite reported anxiety with a new assessment, students were very satisfied and looked forward to undergoing similar assessments in the future. We think that the rigorous process adopted in developing the case scenarios and associated evaluation rubrics, in addition to student orientation and session piloting were instrumental in assuring student familiarity with the new assessment and the level of performance expected from them.…”
Section: Discussionmentioning
confidence: 72%
“…33 Skill-based assessments have also been conducted virtually, including formative and summative OSCE; students were found to perform comparably to those conducted in-person. [34][35] Several studies have been conducted to compare study behaviors and grades of students in on and off campuses licensure examinations, and have found no significant differences in learning outcomes achievement between the two. [36][37][38] The program at Ajman University, United Arab Emirates (UAE) offers a four-year, 160-credit hour Bachelor of Pharmacy degree.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Student performance scores on virtual skills-based assessments compared to in-person have also been published, but a method for evaluating competency of skills performed in a telehealth activity that can be used among different evaluator types is not currently available. [12][13][14] Telehealth etiquette refers to unique behaviors outside of typical professional actions that are used to conduct an effective telehealth visit. 15 Both verbal and non-verbal communication skills are components of telehealth etiquette that lead to increased patient satisfaction and successful interactions.…”
Section: Introductionmentioning
confidence: 99%